Perkembangan manusia ditinjau dari perspektif teori kognitif dan sosial kultural - Hasanah, Maulidiyatul (Maliki Interdisciplinary Journal, 2025)
This paper examines human development from the perspective of Jean Piaget’s cognitive theory and Lev Vygotsky’s sociocultural theory. Piaget emphasized that cognitive development occurs through four stages: sensorimotor, pre-operational, concrete operational, and formal operational, which develop as individuals grow. Meanwhile, Vygotsky emphasized the role of social and cultural interactions in cognitive development, with key concepts such as the zone of proximal development (ZPD) and scaffolding (learning support). This study compares the two theories and their application to learning, and suggests that learning can be more effective by considering both internal and external factors in individual development. This study uses a qualitative method with a literature review approach to comprehensively analyze both theories.